2020
DOI: 10.5194/tc-14-2755-2020
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of synoptic weather types and patterns on energy fluxes of a marginal snowpack

Abstract: Abstract. Synoptic weather patterns are investigated for their impact on energy fluxes driving melt of a marginal snowpack in the Snowy Mountains, southeast Australia. K-means clustering applied to ECMWF ERA-Interim data identified common synoptic types and patterns that were then associated with in situ snowpack energy flux measurements. The analysis showed that the largest contribution of energy to the snowpack occurred immediately prior to the passage of cold fronts through increased sensible heat flux as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The latter have demonstrated that LW radiation is the main component of Rn for snow ablation (from 75 to 86% over the total snow ablation); with net SW radiation accounting for 8-14%. In the same study area, Schwartz et al (2020) showed different Q m contributions on the winter snowpack depending on the CTs. In their study, they found that the dominant energy source for ablation is Rn, contributing a 53-73% of the mean daily energy flux; followed by H that contributed a 16-44% during warm and dry synoptic configurations.…”
Section: Characterization Of the Q M Heat Fluxesmentioning
confidence: 86%
See 1 more Smart Citation
“…The latter have demonstrated that LW radiation is the main component of Rn for snow ablation (from 75 to 86% over the total snow ablation); with net SW radiation accounting for 8-14%. In the same study area, Schwartz et al (2020) showed different Q m contributions on the winter snowpack depending on the CTs. In their study, they found that the dominant energy source for ablation is Rn, contributing a 53-73% of the mean daily energy flux; followed by H that contributed a 16-44% during warm and dry synoptic configurations.…”
Section: Characterization Of the Q M Heat Fluxesmentioning
confidence: 86%
“…Changes in the frequency of the CTs have been associated with the snow trends at low-mid elevations (Buisán et al, 2014) as well as at high elevations of this mountain range (Bonsoms et al, 2021a). To date, only a few studies in other regions have explored the links between the CTs and the snowpack Q m components, such as in the Great Plains (Grundstein and Leathers, 1999) and the Great Lakes of North America (Suriano and Leathers, 2018), in the Tokachi region of Japan (Hayashi et al, 2005) or in the Australian Alps (Schwartz et al, 2020). However, the Q m energy portioning is still unknown in the Pyrenees.…”
Section: Introductionmentioning
confidence: 99%
“…1). The study area experiences a marginal snowpack that commonly forms in June and becomes discontinuous in September (Bormann et al 2012;Thompson and Paull 2017;Schwartz et al 2020b), with an annual mean daily temperature of 4.37°C and an average annual precipitation (rain and snow) of 2165 mm (1976-2005reference period -Xu and Hutchinson 2011. Although wildfire is an agent of disturbance in this area (Thomas et al 2022), particularly in periods of extended drought, large and severe wildfires burning over 100 km 2 of alpine vegetation are rare but were recorded in 1939 and 2003 across the Australian Alps (Williams et al 2008).…”
Section: Study Areamentioning
confidence: 99%